Pengaruh Kualitas Produk, Ekuitas Merek Dan Harga Terhadap Keputusan Pembelian Mobil Toyota Avanza (Studi Kasus Kabupaten Manokwari) - Erwin; Selmi Dedi; Makarius Bajari (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2022)
This study aims to analyze the effect of product quality, brand equity, and price on the purchase decision of Toyota Avanza cars. The sample in this research is who bought a Toyota Avanza in the Manokwari Regency. By using a non-probability sampling method, as many as 120 respondents were identified as research samples. Statistical tests were performed using multiple linear regression analysis. The research method used is quantitative data using primary data obtained by distributing questionnaires to respondents. The results showed that simultaneously, product quality, brand equity, and price variables significantly influence the purchase decision of the Toyota Avanza. Partially, product quality and price variables significantly influence the purchase decision of Toyota Avanza cars, while the brand equity variable does not affect the purchase decisions of Toyota Avanza cars.